Chronic Norovirus Infection as a Risk Factor for Secondary Lactose Maldigestion in Renal Transplant Recipients: A Prospective Parallel Cohort Pilot Study. Issue 6 (June 2017) - Bonani, Marco; Pereira, Rahja M.; Misselwitz, Benjamin; Fehr, Thomas; Wüthrich, Rudolf P.; Franzen, Daniel
Abstract : Background: Chronic norovirus infection is an emerging challenge in the immunocompromised host, in whom it may be asymptomatic or present as chronic diarrhea. The mechanisms of diarrhea in chronic norovirus infection are not well understood, but in analogy to Gardia lamblia and rotavirus infections, secondary lactose maldigestion (LM) might be implicated. Methods: Adult renal transplant recipients who had symptomatic chronic norovirus infection with diarrhea were asked to participate in this prospective parallel cohort study. Renal transplant recipients with otherwise unexplainable chronic diarrhea but absent infection served as control group. In both groups, a lactose hydrogen breath test and a lactose tolerance test were performed after exclusion of primary LM by a negative lactase gene test. Results: Of approximately 800 patients in the cohort of renal transplant recipients at our institution, 15 subjects were included in the present study. Of these, 7 had chronic symptomatic norovirus infection with diarrhea (noro group), and 8 had diarrhea in the absence of norovirus (control group). Lactose hydrogen breath test and lactose tolerance test were positive in all 7 patients (100%) in the noro group, whereas only 1 (12.5%) of 8 patients in the control group had a positive test. Thus, secondary LM was highly prevalent in the noro compared with the control group with an odds ratio of 75.0 (95% confidence interval, 2.6-2153, P = 0.01). Conclusions: This is the first report showing a positive association of chronic norovirus infection and secondary LM. Further studies with larger patient numbers and longer follow-up are needed to test a causative relationship between both entities. Abstract : This small cohort study suggests that secondary lactose maldigesation is associated with chronic symptomatic norovirus infection in kidney transplant recipients. Yet, it is still not known to which extent the intestinal expression of lactase is involved in the pathophysiology of chronic diarrhea.